Multimodality Imaging in Wrist Fractures and Dislocations - Sharma, Madhurima; Choudhury, Shayeri Roy; Sinha, Anindita; Prakash, Mahesh (Indian Journal of Radiology and Imaging, 2025)
Wrist fractures and dislocations are frequently encountered in the emergency department and can cause significant long-term disability. Imaging plays a crucial role in the evaluation of wrist injuries, with conventional radiography being the first imaging investigation. Cross-sectional imaging is playing an increasingly important role in management of wrist injuries. Computed tomography with 3D and multiplanar reformatting capabilities is in particular useful for detailed evaluation of bony injuries and can provide vital information to orthopaedic surgeons for adequate surgical planning. In this article, we provide a brief review of the normal wrist anatomy, imaging appearance, and various patterns of fractures and dislocations commonly encountered in the emergency department.
Keywords: wrist injuries; wrist trauma; radius fractures; radiography; computed tomography